The Effect Of Extrinsic Motivation On Adversity Quotient In Patients With HIV/AIDS - Nursalam Nursalam; Misutarno Misutarno; Yulia Dewi Puspitawati (Universitas Airlangga, 2008)
Introduction: Patients with HIV/AIDS may have various types of psychological responses. It was very difficult situation for them. Difficulty can measured by using Adversity Quotient. As a nurse, we can give extrinsic motivation to bring back the patient HIV/AIDS’s quality of life. The objective of this study was to identify the presence effect of extrinsic motivation on Adversity Quotient in patients with HIV/AIDS in Infectious Disease Intermediateatery Treatment Unit, Dr. Soetomo Hospital, Surabaya.Methods: This study was used a quasy experimental purposive sampling design. The population was taken from ambulatory patients. There were 16 respondents who met to the inclusion criteria. The independent variable was extrinsic motivation and dependent variable was Adversity Quotient. Data were collected by using questionnaire and interview, then analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level p=0.05.Results: The result revealed that there was an effect of extrinsic motivation on Adversity Quotient of patients with HIV/AIDS (p=0.017). The extrinsic motivation was found to have an effect on control response (p=0.027) and origin response (p=0.028), there was no influence of extrinsic motivation on ownership response (p=0.334), reach (p=0.129) and endurance (p=0.161).Conclusion: It can be concluded that the extrinsic motivation with intervention of social support has a positive effect on the improvement of Adversity Quotient in patients with HIV/AIDS. Further studies should measure the effectiveness of Adversity Quotient training on acceptance response in patients with HIV/AIDS.